2018
DOI: 10.1038/s41598-018-35553-7
|View full text |Cite
|
Sign up to set email alerts
|

The autosomal Gsdf gene plays a role in male gonad development in Chinese tongue sole (Cynoglossus semilaevis)

Abstract: Gsdf is a key gene for testicular differentiation in teleost. However, little is known about the function of Gsdf in Chinese tongue sole (Cynoglossus semilaevis). In this study, we obtained the full-length Gsdf gene (CS-Gsdf), and functional characterization revealed its potential participation during germ cell differentiation in testes. CS-Gsdf transcription was predominantly detected in gonads, while the levels in testes were significantly higher than those in ovaries. During the different developmental stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 60 publications
6
22
0
Order By: Relevance
“…The expression pattern has obvious gender dimorphism. This result was consistent with those in Oncorhynchus mykiss, Oryzias latipes and Cynoglossus semilaevis [11,12,15]. The distinct gonad expression pattern in fish indicated that gsdf may have a particular impact on gonad during the period of sex differentiation and maintenance male characteristics.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The expression pattern has obvious gender dimorphism. This result was consistent with those in Oncorhynchus mykiss, Oryzias latipes and Cynoglossus semilaevis [11,12,15]. The distinct gonad expression pattern in fish indicated that gsdf may have a particular impact on gonad during the period of sex differentiation and maintenance male characteristics.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, gsdf transcription is activated directly by dmy, which established the autosomal gsdf as the first male sex initiator in Oryzias latipes [14]. And in Cynoglossus semilaevis, the autosomal gsdf gene play a positive role in germ differentiation and proliferation via influencing genes related to sex differentiation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, expression of gsdf in the same cell types has been observed in several fish species including rainbow trout (Oncorhynchus mykiss), medaka (Oryzias latipes), zebrafish, Nile tilapia (Oreochromis niloticus), Olive flounder (Paralichthys olivaceus), Spotted scat (Scatophagus argus) and Japanese flounder (Paralichthys olivaceus) [24,[42][43][44][45][46][47][48]. Transcripts of gsdf have also been detected within oocytes in Olive flounder, and within spermatogonia and spermatids in Chinese tongue sole (Cynoglossus semilaevis) [46,49]. Although the function(s) of gsdf in male fish seems strongly associated with germ cells, it may differ between species since this gene has been linked to several processes such as proliferation of primordial germ cells and spermatogonia in rainbow trout, sex determination in Oryzias luzonensis, sex differentiation in Chinese tounge sole, and testis differentiation in medaka and Nile tilapia [24,[49][50][51][52][53].…”
Section: Gsdfmentioning
confidence: 83%
“…Transcripts of gsdf have also been detected within oocytes in Olive flounder, and within spermatogonia and spermatids in Chinese tongue sole (Cynoglossus semilaevis) [46,49]. Although the function(s) of gsdf in male fish seems strongly associated with germ cells, it may differ between species since this gene has been linked to several processes such as proliferation of primordial germ cells and spermatogonia in rainbow trout, sex determination in Oryzias luzonensis, sex differentiation in Chinese tounge sole, and testis differentiation in medaka and Nile tilapia [24,[49][50][51][52][53]. Although we do not know the function of Gsdf in salmon testis, it is likely that this protein has one or more roles as described in other fish species.…”
Section: Gsdfmentioning
confidence: 99%
“…Gsdf is a growth factor and as mentioned above, a member of the Transforming growth factor beta (TGF-β) superfamily [24]. Gsdf has mainly been detected in teleosts, but recently also in the coelacanth Latimeria menadoensis [41] [47], and within spermatogonia and spermatids in Chinese tongue sole (Cynoglossus semilaevis) [50]. The gsdf gene was first described as an essential player in proliferation of primordial germ cells and spermatogonia in rainbow trout [24].…”
Section: Gsdfmentioning
confidence: 99%